C4‐Plant Foraging in Northern Italy: Stable Isotopes, Sr/Ca and Ba/Ca Data of Human Osteological Samples from Roccapelago (16th–18th Centuries AD). (13th March 2017) - Lugli, F.; Brunelli, D.; Cipriani, A.; Bosi, G.; Traversari, M.; Gruppioni, G.
Abstract : Human osteological samples ( n  = 23) taken from different anatomical parts of 11 individuals from the early modern (16th–18th century AD) site of Roccapelago (Modena, Italy) were systematically analysed for δ 13 C, δ 15 N and trace elements to investigate their diet. δ 13 C and δ 15 N correlate and show a high variability between individuals, attesting to the dietary contribution of C4 plants. This is supported by pollen analysis of the burial site samples, which revealed the presence of maize. δ 15 N correlates with Sr/Ca, suggesting that the main protein source could have been milk and dairy. We therefore interpret the strong correlation between δ 13 C and δ 15 N as evidence for C4 ‐plant foraging practice and the exploitation of livestock for meat and milk, combined with possible direct intake of C4 plants. The Roccapelago site represents an important case study to track the evolution of the post‐medieval diet and the introduction of maize cultivation in southern Europe, as also attested by historical sources.